Artificial Intelligence and Music Creativity: The Human Element and an Exploration of Possibilities - Benjamin J Guerrero; Raffaella Borasi; David Miller; Blaire Koerner; Zenon Borys; Yu Jung Han; Rachel Roberts (Journal of the Association for Technology in Music Instruction, 2026)
Artificial Intelligence (AI) is widely recognized as a potential game-changer for music-making. However, the direction of these changes and the extent of their impact on the music field will depend on how musicians use AI, which partly hinges on their perceptions of AI and their willingness to engage with it. Debates are ongoing about AI’s impact on creative fields, and we anticipate that musicians’ views on these matters will significantly influence their readiness to incorporate AI into their work. We interviewed 43 participants who use technology in various roles across different music genres to gain insight into their experiences with and perspectives on AI. These interviews revealed a range of perceptions about the potential benefits and risks of using AI in musicians’ creative processes, even among those already accustomed to technology. These perceptions did not always conflict; instead, they complemented one another, reflecting the core values and practices inherent in the diverse roles musicians play as composers, performers, and producers, as well as the different interpretations musicians may have of what constitutes creativity in music. A key finding was asymmetry in musicians' AI acceptance, where those who rejected AI for music creativity often accepted it for tasks typically performed by other creative professionals.
Keywords: artificial intelligence; music creativity; identity; music industry; future of work